ACHIEVING HIGH QUALITY TRANSFORMATIONAL LEADERSHIP THROUGH JENDERAL ACHMAD YANI STYLE - Wulansari, Ririn; Adhiatma, Ardian (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2024)
The purpose of this study is to explore the concept of transformational leadership through Jenderal Achmad Yani style and the implementation challenges face by Jenderal Achmad Yani University Yogyakarta to achieve superior accreditation. The study utilizes qualitative research. The sampling technique uses purpose sampling. Data analysis comprises four concurrent activities: data collection, data reduction, data presentation, and drawing conclusions or verification. The result indicate that Jenderal Achmad Yani University implements transformational leadeship characterized by Jenderal Achmad Yani’s fighting values as role model for lecturers and educational staff. These fighting values are Nationalist, Patriotic, and Heroic. Transformational leadership through Jenderal Achmad Yani style wants to create an academic community that reflects Aditya Mahatma Dhaksa, namely a figure who is clever and wise, big-hearted, capable and expert. The challengers encountered in implementing Jenderal Achmad Yani’s version of transformational leadership include finding ways to internalize Jenderal Achmad Yani’s transformational leadership and transforming his struggle values to the employees of Jenderal Achmad Yani University Yogyakarta. Keywords: Transformational leaderships, Jenderal Achmad Yani’s fighting values, Campus accreditation.